Antioxidant Therapy Reduces Oxidative Stress, Restores Na,K-ATPase Function and Induces Neuroprotection in Rodent Models of Seizure and Epilepsy: A Systematic Review and Meta-Analysis - Anderson Dutra de Melo; Victor Antonio Ferreira Freire; Ítalo Leonardo Diogo; Hérica de Lima Santos; Leandro Augusto Barbosa; Luciana Estefani Drumond de Carvalho (MDPI AG, 2023)
Epilepsy is a neurological disorder characterized by epileptic seizures resulting from neuronal hyperexcitability, which may be related to failures in Na,K-ATPase activity and oxidative stress participation. We conducted this study to investigate the impact of antioxidant therapy on oxidative stress, Na,K-ATPase activity, seizure factors, and mortality in rodent seizure/epilepsy models induced by pentylenetetrazol (PTZ), pilocarpine (PILO), and kainic acid (KA). After screening 561 records in the MEDLINE, EMBASE, Web of Science, Science Direct, and Scopus databases, 22 were included in the systematic review following the PRISMA guidelines. The meta-analysis included 14 studies and showed that in epileptic animals there was an increase in the oxidizing agents nitric oxide (NO) and malondialdehyde (MDA), with a reduction in endogenous antioxidants reduced glutathione (GSH) and superoxide dismutase (SO). The Na,K-ATPase activity was reduced in all areas evaluated. Antioxidant therapy reversed all of these parameters altered by seizure or epilepsy induction. In addition, there was a percentage decrease in the number of seizures and mortality, and a meta-analysis showed a longer seizure latency in animals using antioxidant therapy. Thus, this study suggests that the use of antioxidants promotes neuroprotective effects and mitigates the effects of epilepsy. The protocol was registered in the Prospective Register of Systematic Reviews (PROSPERO) CRD42022356960.